Ex‐vivo analysis of human Natural Killer T cells demonstrates heterogeneity between tissues and within established CD4+ and CD4− subsets. (11th March 2013) - Chan, A. C.; Leeansyah, E.; Cochrane, A.; d' Udekem d' Acoz, Y.; Mittag, D.; Harrison, L. C.; Godfrey, D. I.; Berzins, S. P.
Summary Our understanding of human type 1 natural killer T (NKT) cells has been heavily dependent on studies of cells from peripheral blood. These have identified two functionally distinct subsets defined by expression of CD4, although it is widely believed that this underestimates the true number of subsets. Two recent studies supporting this view have provided more detail about diversity of the human NKT cells, but relied on analysis of NKT cells from human blood that had been expanded in vitro prior to analysis. In this study we extend those findings by assessing the heterogeneity of CD4+ and CD4− human NKT cell subsets from peripheral blood, cord blood, thymus and spleen without prior expansion ex vivo, and identifying for the first time cytokines expressed by human NKT cells from spleen and thymus. Our comparative analysis reveals highly heterogeneous expression of surface antigens by CD4+ and CD4− NKT cell subsets and identifies several antigens whose differential expression correlates with the cytokine response. Collectively, our findings reveal that the common classification of NKT cells into CD4+ and CD4− subsets fails to reflect the diversity of this lineage, and that more studies are needed to establish the functional significance of the antigen expression patterns and tissue residency of human NKT cells.